The Key Network of mRNAs and miRNAs Regulated by HIF1A in Hypoxic Hepatocellular Carcinoma Cells - Liu, Tong; Tang, Jing; Li, Xiaoyu; Lin, Yuan; Yang, Yuma; Ma, Kai; Hui, Zhaoyuan; Ma, Hong; Qin, Yanyan; Lei, Hetian; Yang, Yanhui (Frontiers in Genetics, 2022)
Hepatocellular carcinoma (HCC) is the second most common cause of cancer death worldwide. Hypoxia plays an essential role in the progression of HCC, whereas hypoxia inducible factor-1 (HIF-1) is the key transcription factor. Thus, it is essential to identify the mRNAs and miRNAs regulated by HIF1A. In this study, a human HCC cell line HepG2 was used as a cell model of the HCC, the CRISPR/Cas9 system was used to knock out HIF1A in HepG2 cells, and RNA sequencing was utilized to characterize differentially expressed mRNAs and miRNAs in the HIF1A-knockout HepG2 cells; the identified candidates were then analyzed by GO annotation and KEGG pathway enrichment to study their function and establish PPI network. Quantitative (q) PCR was employed to verify if there were significant differences in expression of mRNAs, and the association of the selected mRNAs expression with immune cell infiltration levels was further analyzed using The Cancer Genome Atlas (TCGA) pan-cancer data. Using RNA sequencing we discovered that there were 1535 mRNAs differentially expressed (P<0.05, |Fold Change|>1.5) in the HIF1A-knockout HepG2 cells, among which there were 644 mRNAs up-regulated and 891 mRNAs down-regulated. GO annotation and KEGG pathway enrichment showed that these mRNAs were involved in glycolysis/gluconeogenesis, PI3K-Akt signaling pathways, and HIF-1 signaling pathways. In addition, we found that there were 309 miRNAs differentially expressed (P<0.05, |Fold Change|>1.5) in the HIF1A-knockout HepG2 cells, of which, there were 213 miRNAs up-regulated and 96 miRNAs down-regulated. Our further analyses uncovered that these miRNAs’ putative targets were involved in Hippo signaling pathway, Axon guidance, and Tight junction. Moreover, PPI network showed that OASL, IL6 and TAF1 were recognized as hub genes with the highest connectivity degrees. Importantly, in the HIF1A-knockout HepG2 cells, qRT-PCR data confirmed the selected mRNAs’ changes revealed by RNA sequencing, and with TCGA pan-cancer data we revealed that expressional levels of these three genes, LUM, SCOC and CCL2, were associated with immune cell infiltration levels. In summary, the identified potential key network of mRNAs and miRNAs regulated by HIF1A in the HCC cells suggests a key role of HIF1A in the tumorigenesis of HCC.